EVALUATING DESIGN AND MATERIAL EFFECTS ON COMMERCIAL HIP IMPLANT PERFORMANCE USING FINITE ELEMENT ANALYSIS - Nikam, Nishant; KN, Chethan; Shenoy B, Satish; Keni, Laxmikant G; Shetty, Sawan; Bhat N, Shayamasunder (Journal of Applied Engineering Science, 2025)
This study presents a comprehensive finite element analysis of commercial hip implants, emphasizing the influence of geometric configurations and material selection on structural performance under static loading. The investigation considered two distinct stem geometry-oval and mixed profiles and evaluated two biomaterials, cobalt-chromium alloy and Ti-6Al-4V alloy, in metal-on-metal configurations. Commercial hip implant models were developed using CREO software and meshed with optimized grid parameters, adhering to ASTM F2996-13 standards for boundary and load conditions. The primary performance metrics analyzed included total deformation, von Mises stress, and elastic strain, indicating structural stability and load-bearing capacity. The results revealed that the oval CoCr stem demonstrated superior mechanical characteristics, exhibiting the lowest deformation (0.078 mm), stress (243.24 MPa), and elastic strain (0.00121 mm/mm), underscoring the biomechanical advantage of the optimized geometry combined with stable biomaterials. The findings highlight that implant geometry significantly affects load distribution and stress concentration, with oval geometries promoting more efficient load transfer. Furthermore, the study underscores the critical role of material properties of CoCr alloys, offering enhanced structural integrity over Ti-6Al-4V. Although the current analysis omits wear, micromotion effects, and surface coating influences, the results lay a foundation for future dynamic loading models for wear analysis and coating strategies. Integrating these parameters could further improve implant longevity and patient outcome. Ultimately, this research advances the understanding of design strategies to optimize implant durability, reduce revision rates, and inform future orthopedic implant innovations.
Keywords: Hip implant; Finite element analysis; Biomaterials; Static analysis; von Mises stress; Total hip replacement